Polyphenolic compounds and anthocyanin content of Prosopis nigra and Prosopis alba pods flour and their antioxidant and anti-inflammatory capacities - Perez, Maria Jorgelina (2014)
The aim of this study was to determine the content of total free and bound phenolic, free and bound flavonoid, anthocyanin, alkaloid and the profiles of polyphenols of the edible ripe pods of Prosopis alba and Prosopis nigra. P. alba flour showed significantly higher total (sum of Free- and Bound) phenolic content and total flavonoid compounds than P. nigra (P < 0.05) while P. nigra had higher concentrations of anthocyanins than P. alba (P < 0.05). The P. nigra flour shows a pattern characterized by the occurrence of anthocyanins (principally cyanidin-3-glucoside) as well as 14 flavonoid glycosides, with higher chemical diversity than P. alba, who shows 8 flavonoid glycosides as relevant constituents. The main compounds were quercetin O-glycosides and apigenin-based C-glycosides. The phenolic composition of two South American algarrobo pod flour is presented for the first time. The colour of the algarrobo pods is related to the content of anthocyanins. P. nigra pods having higher content of anthocyanins are darker (purple) than those of P. alba (light brown). Furthermore, the free sugar polyphenolic extracts of P. nigra and P. alba (phenolic-enriched Amberlite-retained fraction) as well as anthocyanins enriched extracts from P. nigra showed free radical scavenging activity. The P. nigra polyphenolic extracts showed activity against a pro-inflammatory enzyme (cyclooxygenase). In conclusion, algarrobo pods meal differing in colour contained biologicall active polyphenols, with possible positive impact in human health.